Interferon suppresses pinocytosis but stimulates phagocytosis in mouse peritoneal macrophages: related changes in cytoskeletal organization (The Rockefeller University Press, 1984)
Treatment of thioglycolate-elicited macrophages with mouse beta- interferon markedly reduces pinocytosis of horseradish peroxidase and fluorescein isothiocyanate (FITC)-dextran but stimulates phagocytosis of IgG-coated sheep erythrocytes. Experiments with FITC-dextran have revealed that the overall decrease in pinocytosis is due to a nearly complete inhibition of pinocytosis in a large fraction of interferon- treated macrophages. In the remaining cells pinocytosis continues at a rate similar to that in untreated control cells. A considerable reduction in the number of cells pinocytosing FITC-dextran was observed within 12 h from the beginning of interferon treatment. Measurement of the overall level of pinocytic activity with horseradish peroxidase showed a progressive decline through 72 h of treatment. In the interferon-sensitive subpopulation, there were marked changes in cytoskeletal organization. Microtubules and 10-nm filaments were aggregated in the perinuclear region while most of the peripheral cytoplasm became devoid of these cytoskeletal structures as observed by fluorescence and electron microscopy. In addition, interferon treatment of macrophages appeared to disrupt the close topological association between bundles of 10-nm filaments and organelles such as mitochondria, lysosomes, and elements of the Golgi apparatus and endoplasmic reticulum. Such alterations in the distribution of microtubules and 10- nm filaments were not seen in the interferon-insensitive subpopulation. We have investigated the mechanism of the interferon-induced enhancement of phagocytic activity by binding IgG-coated sheep erythrocytes to mouse peritoneal macrophages at 4 degrees C and then initiating a synchronous round of ingestion by warming the cells to 37 degrees C. Thioglycolate-elicited macrophages that had been treated with mouse beta-interferon ingested IgG-coated erythrocytes faster and to a higher level than control cells in a single round of phagocytosis. In interferon-treated cultures, phagocytic cups became evident within 30 s of the shift of cultures from 4 degrees to 37 degrees C, whereas in control cultures, they appeared in 2 min. Cytochalasin D, an inhibitor of actin assembly and polymerization, abolished phagocytic activity in both control and beta-interferon-treated macrophages. However, to inhibit phagocytosis completely in thioglycolate-elicited interferon-treated macrophages, twice as much cytochalasin D was required in the treated as in control cultures.(ABSTRACT TRUNCATED AT 400 WORDS)